PENGEMBANGAN MEDIA PEMBELAJARAN PAI BERBASIS ANDROID MENGGUNAKAN APLIKASI BETA-Q PADA MATERI HUKUM TAJWID QALQALAH DI KELAS VII MTS NEGERI 2 LUMAJANG - Achmad Khoiruddin; Qurroti A'yun; Indhra Mustofa (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Along with the times, many challenges arise in the world of education. The development of increasingly advanced technology which can now be accessed via smartphones encourages efforts to create learning media that can be accessed via smartphones. At MTs Negeri 2 Lumajang, there is still no media used for the learning process, only face-to-face use is available which will certainly be boring, especially when the Covid 19 pandemic yesterday required online learning at home. This study uses Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Based on the results of the study, the results of the media expert validation were 76%, the material expert validation results were 84%, the subject teacher validation results were 88%, and the student test results were 92.72%. Thus, it can be concluded that the Android-based PAI learning media using the BETA-Q application on tajwid qalqalah law material in class VII MTs Negeri 2 Lumajang is very feasible to use.